Henry VIII & his six wives - Guy, John. (Great Britain : ticktock Pub., 1997)
A brief, color-illustrated biography of England's King Henry VIII that describes his six marriages, his break with the Church of Rome, his patronage of the arts, his palaces, his relations with the rest of Europe, the dissolution of the monasteries, and other related topics.
Includes index.
8.7
5-8
Keywords: Anne Boleyn, -- Queen, consort of Henry VIII, King of England, -- 1507-1536.; Anne, -- of Cleves, Queen, consort of Henry VIII, King of England, -- 1515-1557.; Catharine Howard, -- Queen, consort of Henry VIII, King of England, -- d. 1542..; Catharine Parr, -- Queen, consort of Henry VIII, King of England, -- 1512-1548.; Catharine, -- of Aragon, Queen, consort of Henry VIII, King of England, -- 1485-1536.; Henry -- VIII, -- King of England, -- 1491-1547.; Jane Seymour, -- Queen, consort of Henry VIII, King of England, -- 1509?-1537.; Kings, queens, rulers, etc; Great Britain -- History -- Henry VIII, 1509-1547.; Great Britain -- Kings and rulers -- Biography; Great Britain -- History -- 1485-1603, Tudors